Effectiveness of Pelvic Floor Exercises on Urinary Incontinence in Urology Surgery Patients: Systematic Review - Asroful Hulam Zamroni; Elvi Kurnia Damayanti; Johanes Eban B. Dorman; Rizki Nur Azhadin; Ika Yuni Widyawati (Universitas Tribhuwana Tunggadewi, 2025)
Urological surgery is a medical procedure in treating disorders of the urinary tract, reproductive organs, and other urogenital systems that have the most common risk of complications in the form of urinary incontinence. This systematic review aimed to assess the effectiveness of pelvic floor exercises are in reducing the occurrence of urinary incontinence among patients who have undergone urological surgery. Four databases, including Scopus, PubMed, ProQuest and Sciencedirect, were reviewed for relevant articles published from 2020 to 2025. The literature search was conducted using keywords such as